Strenghtening The Family Role In Preventing Covid-19 Local Transmission in Langsa Lama District Langsa City Aceh Province - Diza Fathamira Hamzah; Hamidah Hanim (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
Langsa is one of the area in Aceh Province which is classified as a COVID-19 red zone. On October 21, 2020, confirmed cases of COVID-19 had increased, as much as 242 cases. This enhancement in cases occurs because most of the people of Langsa City do not have a good knowledge of COVID-19 prevention, which generally occur due to local transmission. The healthy lifestyle in the family environment as the smallest scope in society is considered to minimize a COVID-19 local transmission. This study aims to enhance public by measuring maternal knowledge in preventing local transmission of COVID-19. The research design is a quasi-experimental design with one group pre and post test design. The population in this study were 1,864 families and as many as 95 families were drawn as samples. The sampling technique was drawn by using cluster random sampling method. The data were collected by using a questionnaire. Data analysis was performed by paired T test with 95% confidence interval. The result showed that family strengthening as measured by increasing the knowledge of family mothers significantly affects to prevent local transmission of COVID-19 in the Langsa Lama sub-district (p-value 0.000).